2022
DOI: 10.1177/09673911221109422
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of electrospun nanofiber membrane from polyvinyl alcohol loaded with Glycyrrhiza glabra extract

Abstract: This study was designed to form an electrospun nanofiber membrane generated from different ratio of polyvinyl alcohol (PVA) and Glycyrrhiza glabra (licorice) extract. The electrospinning process was used to fabricate the nanofiber membrane using maximum amount of licorice extract solution. 90% licorice extract solution was successfully electrospun to fabricate nano membrane with 10% PVA solution. Antibacterial, cytotoxicity, scanning electron microscope (SEM) test were performed on resulted sample. The outstan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Because, previous studies regarding natural polymer based nanofibrous mat showed average diameter range 175–245 nm and so on. 9,12,60…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because, previous studies regarding natural polymer based nanofibrous mat showed average diameter range 175–245 nm and so on. 9,12,60…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a previous study was carried out to assess the biocompatibility of PVA/licorice nanofibrous mat and the result showed good biocompatibility of the developed mat. 60 To know the actual activities of the chemical compounds of licorice extracts and chitosan against both bacteria (gram-negative and gram-positive), further studies are required.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ziziphus jujube Mill. [13], Aloe vera [14] and Glycyrrhiza glabra [15]), non-steroidal antiinflammatory drug (sodium salicylate, diclofenac sodium, indomethacin and naproxen) for transdermal drug delivery, and to improve the solubility of the poorly water-soluble drug Probucol [16].…”
Section: Introductionmentioning
confidence: 99%